Pengaruh Kompetensi Profesional Kepala Sekolah dan Guru Terhadap Motivasi Belajar Siswa Kelas VII di SMP BP Amanatul Ummah Pacet-Mojokerto - Jazur Rohim; Abu Darim (Universitas Palan, 2025)
This research was conducted with a quantitative descriptive method approach, regarding: 1. How is the influence of the principal's professional competence on student learning motivation? 2. How is the effect of teacher professional competence on student learning motivation? 3. How is the effect of the professional competence of principals and teachers simultaneously on student motivation? The data collection technique used is to provide a set of questions or written statements to respondents to answer them with questionnaire instruments (questionnaires),observation sheets and documents that have previously been validated and reliably. Data analysis uses data description, analysis prerequisite tests consisting of tests of normality, heteroscedasticity and multicollinearity, as well as testing data hypotheses consisting of simple and multiple regressions. The results of the study found that: (1) The effect of the principal's professional competence on student learning motivation at the Amanatul Ummah Islamic Boarding School is 36.1% with t count 3,977> t table 2,051, (2) The effect of teacher professional competence on student learning motivation in Junior High School Based on Amanat Umat Islamic Boarding School 34.4% with t count 3.85> t table 2.051, and (3) the simultaneous influence of school and teacher professional competence on student learning motivation in Amanatul Ummah Islamic Junior High School is 55% with count 16.52> f table 3,350.